New Perspectives in Medical Records : Meeting the Needs of Patients and Practitioners - Rinaldi, Giovanni (Springer International Publishing : Imprint: Springer, 2017)
This book provides innovative practical suggestions regarding the production and management of medical records that are designed to address the inconsistencies and errors that have been highlighted especially in relation to national eHealth programs. Challenges and lessons that have emerged from the use of clinical information and the design of medical records are discussed, and principles underpinning the implementation of health IT are critically examined. New trends in the use of clinical data are explored in depth, with analysis of issues relating to integration and sharing of patient information, data visualization, big data analytics, and the requirements of modern electronic health records. The spirit pervading the book is one of co-production, in which the needs of practitioners are taken into account from the outset. Readers will learn the basic concepts of how clinical information emanating from the doctor-patient relationship can be effectively integrated with genetic and environmental data and analyzed by complex algorithms with the goal of improving medical decision making and patient care. The book, written by European experts and researchers, will be of interest to all stakeholders in the field, including doctors, technicians, and policy makers.
Keywords: Medicine.; General practice (Medicine).; Health administration.; Health informatics.; elektronické knihy; electronic books